To determine the relationship between sensory marketing and impulse buying behavior on general merchandises among Generation Z in Malaysia - Law, Sze Yin; Sim, Zhi Wei (2024)
This study employs quantitative research methods to examine the correlation between impulse buying behaviour and sensory marketing in the general retail industry, with a specific emphasis on Generation Z customers. The study utilises a well-organised questionnaire to collect data from 386 participants, with the objective of determining the impact of several sensory marketing aspects (sight, sound, smell, and touch) on impulsive purchasing habits. The research aims to determine the most influential sensory triggers that drive unexpected purchases by analysing survey responses using statistical methods such as correlation and regression analysis. The findings suggest that out of the sensory marketing factors investigated, only visual cues (sight) exert a notable influence on impulsive purchasing behaviour. The study revealed a significant positive relationship between visual components and impulsive buying, indicating that the visual attractiveness plays a crucial role in driving impulsive purchases among Generation Z consumers. However, this study found no significant correlations between impulse buying behaviour and the senses of sound, smell, and touch. The findings emphasise the significant influence of visual marketing methods on the purchasing choices of Generation Z. Retailers and marketers can utilise this understanding by prioritising visually captivating components to amplify consumer involvement and boost sales. The study's findings underscore the need of employing a focused strategy in sensory marketing, namely in creating advertising materials and instore exhibits that captivate the visual faculties of young customers. This research provides useful insights to the realm of consumer behaviour and marketing strategy, To Determine the Relationship Between Sensory Marketing and Impulse Buying Behavior on General Merchandises Among Generation Z in Malaysia presenting practical implications for enhancing sensory marketing methods to meet the preferences of Generation Z more effectively. Keywords: Impulse Buying Behavior, Sensory Marketing, General Merchandises, Generation Z, Physical Store. HF5410-5417.5 Marketing. Distribution of products.